The Influence of Monopoly Usage on Accounting Learning Outcomes of High School Students - Safitri, Wanda; Susilo, Agus (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to determine the effect of using monopoly learning media on the accounting learning outcomes of Muhammadiyah 23 Jakarta high school students. This study employs a type of quantitative research quasi-experiment method with a non-equivalent control group design. The population of this study consists of all 11th-grade students at Muhammadiyah 23 East Jakarta High School, which totals 150 students. The samples were 11th-grade Science class 2 with 30 students as the experimental group and 11th-grade Social Studies class 3 with 30 students as the control group. The sampling technique in this study was nonprobability sampling, namely purposive sampling. The data used in the research is quantitative data with primary and secondary data sources. The research instrument utilized is a test in the form of a pretest and post-test. Data analysis conducted in this study includes descriptive statistics analysis and a t-test. Based on the hypothesis test conducted using the T-test, the sig. (2 tailed) of 0.002. These results show the sig value. (2 tailed) of 0.002 0.05 so that Ho is rejected and Ha is accepted. Based on the results of research conducted by the researcher, it can be concluded that there is a significant influence on the use of monopoly learning media on the accounting learning outcomes of class XI students of SMA Muhammadiyah 23 Jakarta.